Fine Needle Diathermy and Intraestromal Bevacizumab: A Combined Treatment for Corneal Neovascularization - Patricia Bayo-Calduch; Jorge Vila-Arteaga; Jose Francisco Marí-Cotino (The Ophthalmology, 2016)
Purpose: The cornea is an avascular and transparent tissue due to a high level of anti-angiogenic molecules. Any alteration of the balance between angiogenic and anti-angiogenic molecules may cause corneal neovascularization which may lead to reduced visual acuity. Now-a-days there is a variety of treatments for corneal neovascularization. The aim of the present paper is to evaluate the efficacy and security of intraestromal bevacizumab combined with fine needle diathermy on corneal neovascularization. Method: A 44-year-old patient presented with relapsing corneal ulcer and corneal inferior neovascularization resistant to conservative treatment, which led us to treat with fine needle diathermy and intraestromal bevacizumab. Result: One week after the treatment, some intraestromal hemorrhages still remained but epitelial edema had solved, observing afterwards a complete resolution of hemorrhages and angioregression of treated corneal new vessels. Conclusion: Fine needle diathermy associated with intraestromal bevacizumab should be considered as a simple, effective and low cost therapeutic option for corneal neovascularization.